Plant-growth promoting rhizobacteria on peanuts: Effects on yield determination, growth rates, and radiation use efficiency in field trials in Argentina - Bigatton, Ezequiel Darío; Ayoub, Ibrahim; Palmero, Francisco; Castillejo Sánchez, María Ángeles; Vázquez, Carolina; Lucini, Enrique Iván; Haro Juarez, Ricardo Javier (Elsevier, 2025)
Plant growth-promoting rhizobacteria (PGPR) are an alternative to enhance crop productivity and reduce the environmental footprint in crop production systems. The main objective of this study was to determine the effects of PGPR inoculation on peanuts under field conditions. The specific objectives were to: i) assess the impact on yield generation and its components, ii) determine the effects on crop and pod growth rates and biomass partitioning, and iii) analyze the effects of PGPR inoculation on radiation use efficiency. The experiments (Expn) were conducted under field conditions during two growing seasons (2019–2020 and 2020–2021) in two locations in the center of Argentina. Two peanut cultivars (CV) (ASEM 400 INTA and Granoleico) were sown on four contrasting sowing dates (SD) (Oct-15, Nov-11, Nov-29, and Dec-10). The effect of three PGPR strains and Bradyrhizobium japonicum on different crop traits was evaluated. The studied PGPR were Bacillus velezensis, strains RI3 and SC6, and Pseudomonas psychrophila, strain P10. A control treatment without inoculation was included in the Expn. In Exp1 and Exp3, treatments were arranged in a split-plot randomized complete block design with cultivars in the main plot and PGPRs in the sub-plot. In Exp2, a split-split-plot randomized complete block design was set, where the main plot was sowing dates, cultivars in the sub-plots, and PGPRs in the sub-sub-plot. In all the Expn, three replicates were set with 36.4 m2 plots. PGPR improved peanut yield by 33% on average. The seed yield (SY) was strongly associated with the seed number (SN) in both CVs R2 = 0.88 – 0.90; p < 0.0001). The seed weight (SW) increased with PGPR (+18%; 0.64 g seed-1), especially in early SD. The SN was positively (p < 0.0001) associated with CGRR3-R6.5 (R2 = 0.66 – 0.70) and pod growth rate (PGRR3-R6.5; R2 = 0.71 – 0.63). Furthermore, the PGPR increased the CGRR3-R6.5 by 28% (14 – 26 g m-2 day-1) and the PGRR3-R6.5 by 30% (6 – 14 g m-2 day-1). High growth rates were associated with a higher harvest seed index (HIS) (0.19 – 0.20). The PGPR application increased the RUE by 12 – 18%, mainly driven by total biomass (TB) increases. These PGPR-enhanced growth traits could be partly explained by increased levels of Auxins (22%), Gibberellins (23%), and Cytokinins (27%). This study evidences the effects of PGPR on improving peanut production via increased crop growth rates and radiation use efficiency.